PENGARUH PERSEPSI WAJIB PAJAK TENTANG PENERAPAN PP NO 23 TAHUN 2018, PEMAHAMAN PERPAJAKAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM DIMAKASASAR - Carolus Askikarno Palalangan; Ribka Pakendek; Luther P. Tangdialla (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2019)
The purpose of this study was to determine the influence of: (1) Implementation Of PPNo. 23 Tahun 2018 for tax compliance of MSMEs, (2) the understanding of taxation for tax compliance of MSMEs, (3) Ttax penalties for tax compliance of MSMEs, and also (4) Implementation Of PP No. 23 Tahun 2018 And The Understanding Of Taxation And Tax Penalties together on Tax Compliance of MSMEs. The population in this study is the MSMEs in the city of Makassar. The samples in this research are taking from 50 MSMEs. The data collecting method is by giving questionnaire. Analysis prerequisite test included normality test, linearity test, heteroscedasticity test, and multicolinearity test. The data analysis technique used a simple and multiple linear regression analysis. The result of the research shows Implementation Of PP No. 23 Tahun 2018 positively influance and the significance towards the tax compliance. It is proved that the regression coefficient is positive 0,408 and t count is greater compared to t table (3,511 > 2,01290) in the significance of 0,001< 5%. The understanding of taxation positively influence and significant toward the tax compliance. It isproved that the the regression coefficient is positive 0,215 and t count is greater compared to t table (2,079> 2,01290) in the significance of 0,043< 5%. Tax penalties positively influenceand significant toward the tax compliance. It is proved that the regression coefficient is positive 0,297 and t count is greater compared to t table (2,468 > 2,01290) in the significance of 0,017 < 5%. Implementation Of PP No. 23 Tahun 2018, the understanding taxation and taxpenalties positively together influenced toward the tax compliance. It is proved that the significance of 0,000<5% and F count is greater compared to F table (13,270 > 2,80) in the significance of 0,000 < 5%.